Assistance in The Implementation of Peer Group Counseling for Tegal City Genre Volunteers as an Effort to Prevent Early Marriage During the Covid 19 Pandemic - Herdiani, Renie Tri; Hartinah DS, Sitti; Efani, Dita (ASEAN Journal of Empowering Community, 2022)
This community service activity is held based on the reality that many early marriages seem “forced” and end up with less comfortable things, especially in terms of psychology. Based on this, we want to share information on the impact of early marriage in terms of psychological, social, economic, health and o, and their. The socialization from related parties makes us want to do service to provide selling assistance counseling teenagers have insight into the impact of promiscuity and young marriage so that teenagers avoid various problems in navigating life. The target of this service is the genre volunteers of the city of Tegal of junior-high school age as the subjects of the service. The service implementation procedure uses three methods, namely the three lects: lecture, peer group counseling assist counseling the activity process. Many parts activation gave a positive response, namely by asking our team many questions about various things related to the positive and negative impacts of early marriage, so we can conclude that this mentoring activity is beneficial, especially in this case volunteers a genre that is still common with the effects of early marriage. We hope that after this peer group counseling assistance activity, all participants can resocialize it to their friends in their environment so that young people can understand and consider the positive and negative impacts of getting married at a young age. In addition, parental supervision also needs to be improved.